(untitled) (Al-Academy, 2022)
Color is one of the most important elements involved and contributing mainly to designs and visual works, whether they are fixed or mobile, for internal spaces through what color gives it the possibilities on the physical and intellectual level, if the process is linked to the functional performance or the aesthetic value, which is thus included within the system of processors and basic works in Designing the interior spaces and highlighting the functional and aesthetic aspects of them through the executed designs that are linked to certain techniques and mechanisms. Therefore, they are processed according to the references and pressure structures or the creation and modern dealing with materials and designs to implement operations in highlighting the functional and aesthetic aspects of the interior spaces. The introduction to the research includes the methodological framework for research and finding concepts and definitions for some The terms that were mentioned in the title of the research, then the theoretical framework, which included two sections: the first topic (color - the essence of the concept and work), and the second topic (the work of color in treatments for the design of interior spaces) leading to a number of results and conclusions, the most important of which are:1. Colors functioned as functional, symbolic and aesthetic at the same time through the various relationships between color and the rest of the visual elements.2. The process of highlighting the functional and aesthetic aspects of the process of employing colors in the inheritance, pressure structures, and cultural and artistic references was linked.